2010
DOI: 10.2202/1542-6580.2018
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Zinc Ions from Water Using Emulsion Liquid Membrane

Abstract: In the present study, the removal of zinc from synthetic waste water using emulsion liquid membrane extraction technique was investigated. Synthetic surfactant solution is used as the emulsifying agent. Diphenylthiocarbazon (dithizone) was used as the extracting agent dissolved in carbon tetrachloride as the organic solvent and sulfuric acid is used as the stripping agent. The parameters that influence the extraction percentage of Zn+2 were studied. These are the ratio of volume of organic solvent to volume of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Increasing the residence time leads to water transport into the internal phase, membrane swelling and emulsion breakage [54–55] . Therefore, with arsenic leakage from the internal phase to the external phase, the removal rate of arsenic decreases [56] . These results are consistent with the previous studies that showed the effect of longer contact time on emulsion breakage [57–58] …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Increasing the residence time leads to water transport into the internal phase, membrane swelling and emulsion breakage [54–55] . Therefore, with arsenic leakage from the internal phase to the external phase, the removal rate of arsenic decreases [56] . These results are consistent with the previous studies that showed the effect of longer contact time on emulsion breakage [57–58] …”
Section: Resultssupporting
confidence: 89%
“…[54][55] Therefore, with arsenic leakage from the internal phase to the external phase, the removal rate of arsenic decreases. [56] These results are consistent with the previous studies that showed the effect of longer contact time on emulsion breakage. [57][58] To evaluate the stability of the emulsions at rest, emulsions were prepared by employing the three mentioned carriers.…”
Section: Effect Of Carrier Type and Residence Timesupporting
confidence: 93%
“…For instance, leaf, stem bark, and peel extracts exerted both in vitro and in vivo activity against the gastrointestinal parasites Schistosoma mansoni [232], Ascaris suum [233], and Giardia lamblia [309]. These effects might be due to pelletierine alkaloids, unusual alkaloids which, among others, paralyze tapeworms so that they are easily expelled from the body by using a laxative [310]. Other compounds isolated from the fruit such as the phenolics gallagic acid and punicalagins exhibited in vitro activity against the malaria parasite Plasmodium falciparum [184].…”
Section: Lythraceae-punica Granatum Lmentioning
confidence: 99%
“…These points have clearly explained the importance of fixing some limits for these heavy metals in drinking and waste waters. Treatment methods to reach the fixed limit (5ppm) include chemical precipitation and other separation methods [5][6][7][8][9][10][11][12] . In this study we are interested in the treatment of the cyanide-free alkaline zinc-plating effluent, where cyanide may be replaced by complexing or chelating agents such as sodium gluconate, triethanolamine or polymeric amines.…”
mentioning
confidence: 99%